Chiral Landau levels in Weyl semimetal NbAs with multiple topological carriers - Xiang Yuan (Nature Portfolio, 2018)
How the carriers behave in a Weyl semimetal if they occupy the lowest Landau level remains elusive. Here, the authors report evidences of electrons occupying zeroth chiral Landau levels with distinct linear dispersion behaviors for two inequivalent Weyl nodes in a Weyl semimetal NbAs.